PENINGKATAN KETERAMPILAN MENULIS TEKS BIOGRAFI MENGGUNAKAN METODE INQUIRI PADA SISWA KELAS X SMA NEGERI 5 PONTIANAK - Karina Karina; Syambasril Syambasril; Ahmad Rabi’ul Muzammil (Universitas Tanjungpura, 2021)
AbstractThis study aims to improve the skills of writing biographical texts using the inquiry method in class X IPS 2 SMA Negeri 5 Pontianak. This study consisted of two cycles, namely cycle I and cycle II with the research subjects of class X IPS at SMA Negeri 5 Pontianak. The implementation of this research was carried out based on the problems found in learning to write biographical texts, namely the low student learning outcomes. The research method used in this research is descriptive method to reveal the real situation in the form of the process and learning outcomes about improving the skills of writing biographical texts using the inquiry method in class X IPS 2 SMA Negeri 5 Pontianak. The increase in student learning outcomes from cycle I to cycle II has increased. The results of the test cycle I obtained an average value of 70.30 and the test cycle II increased with an average value of 81.78. From this study it can be concluded that the use of the inquiry method can improve the ability to write biographical texts of class X IPS 2 SMA Negeri 5 PontianakKeywords: Inquiry Method, Writing Biographical Text, X Grade High School Student